2021
DOI: 10.1111/jade.12356
|View full text |Cite
|
Sign up to set email alerts
|

How Do I Know What I See Until I Hear What I Say?

Abstract: Whereas we acknowledge that drawing as process and product within the visual arts is complex and wide ranging, this study concentrates on testing the effectiveness of different pedagogical strategies for enhancing accuracy as a learning objective in drawing from observation. Based on our collective experience teaching observational drawing, we hypothesised that describing a scene verbally in advance of drawing it would encourage a more sophisticated appraisal of the scene and result in a more accurate represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It was hypothesized by the experiments that a verbal description of the scene before drawing would lead to a more complex assessment of the scene. Validation indicated that the accuracy of the drawing increased as the number of words used in the description increased [12]. Scholars have transformed traditional teaching modules into student-centered learning environments using a participatory design experience approach.…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized by the experiments that a verbal description of the scene before drawing would lead to a more complex assessment of the scene. Validation indicated that the accuracy of the drawing increased as the number of words used in the description increased [12]. Scholars have transformed traditional teaching modules into student-centered learning environments using a participatory design experience approach.…”
Section: Introductionmentioning
confidence: 99%